Manav Sansadhan Vikas: samvedansheel prashashan - Misra, Durga Shanker
The article is in Hindi. Author discusses the concept of welfare state and describes the various aspects related to making the administration sensitive and people centred
Keywords: India; Public Administration; Administration; HRD; Welfare State